Recent Situation and Progress in Biorefining Process of Lignocellulosic Biomass: Toward Green Economy - Cheng, Yu-Shen; Mutrakulcharoen, Parita; Chuetor, Santi; Cheenkachorn, Kraipat; Tantayotai, Prapakorn; Panakkal, Elizabeth Jayex; Sriariyanun, Malinee (Applied Science and Engineering Progress, 2020)
Towards the rising trends of Bio Economy, Circular Economy and Green Economy (BCG economy) concept, biorefining process has been developed continuously to improve the utilizations of unused lignocellulosic biomass to produce value-added chemicals and products. During the early era of biorefining process, the major focuses of biorefining products were dedicated to biofuels, especially bioethanol and biobutanol due to the coherent situation of rising crude oil price. Currently, the targeted products of biorefining processes are directed to platform chemicals, which their purposes are not limited to fuels, but are expanded to various downstream industries. However, most of developed processes are still unable to overcome the numbers of concerns, especially economic issue and scaling up technology. This review explores the recent pretreatment technologies of lignocellulosic biomass and addresses the direction of development to provide the updated situation of biorefining process for peer-researchers and related industries.